2020
DOI: 10.7759/cureus.11125
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomegaly Masquerading as a Pediatric Thymoma: A Case Report

Abstract: Thymoma is a very rare pediatric tumor, accounting for less than 1% of all childhood mediastinal tumors with scant literature, and only 23 pediatric cases were identified by a pediatric tumor surveillance registry between 1973 and 2008. In contrast to adult thymomas, pediatric thymomas have an aggressive tendency, though the majority is discovered as incidental findings. Patient presentations to the emergency department (ED) are often subtle and non-specific such as dyspnea, cough, and chest pain, requiring a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thirty-two articles, twenty-three case reports [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], seven small retrospective case series [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ], and two reviews of the literature [ 11 , 53 ] were identified, for a total of eighty-two pediatric thymomas ( Table S1 ). Patients ranged in age from 0.9 to 17 years, with a mean age of 10.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two articles, twenty-three case reports [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], seven small retrospective case series [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ], and two reviews of the literature [ 11 , 53 ] were identified, for a total of eighty-two pediatric thymomas ( Table S1 ). Patients ranged in age from 0.9 to 17 years, with a mean age of 10.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Summary of cases. References [ 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%